Rational engineering of the Trichoderma reesei RUT-C30 strain into an industrially relevant platform for cellulase production - Fonseca, Lucas Miranda (Biotechnol Biofuels, 2020)
BACKGROUND: The path for the development of hypersecreting strains of Trichoderma reesei capable of producing industrially relevant enzyme titers remains elusive despite over 70 years of research and industrial utilization. Herein, we describe the rational engineering of the publicly available T. reesei RUT-C30 strain and a customized process for cellulase production based on agroindustrial by-products. RESULTS: A CRISPR/Cas9 system was used to introduce six genetic modifications in RUT-C30. Implemented changes included the constitutive expression of a mutated allele of the cellulase master regulator XYR1, the expression of two heterologous enzymes, the β-glucosidase CEL3A from Talaromyces emersonii and the invertase SUC1 from Aspergillus niger, and the deletion of genes encoding the cellulase repressor ACE1 and the extracellular proteases SLP1 and PEP1. These alterations resulted in a remarkable increase of protein secretion rates by RUT-C30 and amended its well described β-glucosidase deficiency while enabling the utilization of sucrose and eliminating the requirement of inducing sugars for enzyme production. With a developed sugarcane molasses-based bioprocess, the engineered strain reached an extracellular protein titer of 80.6 g L(−1) (0.24 g L(−1) h(−1)), which is the highest experimentally supported titer so far reported for T. reesei. The produced enzyme cocktail displayed increased levels of cellulase and hemicellulase activities, with particularly large increments being observed for the specific activities of β-glucosidase (72-fold) and xylanase (42-fold). Notably, it also exhibited a saccharification efficiency similar to that of a commercially available cellulase preparation in the deconstruction of industrially pretreated sugarcane straw. CONCLUSION: This work demonstrates the rational steps for the development of a cellulase hyperproducing strain from a well-characterized genetic background available in the public domain, the RUT-C30, associated with an industrially relevant bioprocess, paving new perspectives for Trichoderma research on cellulase production.